1993
DOI: 10.1007/bf00209526
|View full text |Cite
|
Sign up to set email alerts
|

Serotypes and colonization factors of enterotoxigenic Escherichia coli isolated in various countries

Abstract: One hundred and six enterotoxigenic E. coli (ETEC) isolated from many geographical areas were serotyped and investigated for the presence of colonization factor antigens CFA/I and CFA/II, the expression of mannose-resistant haemagglutination (MRHA) and the levels of surface hydrophobicity. CFA/I was found in 6 (17%) of 36 LT+STa+ strains and in 15 (54%) of 28 STa+ strains; CFA/II was found in 16 (44%) of 36 LT+STa+ strains. None of 42 LT+ strains showed CFA/I or CFA/II. CFA/I was found in ETEC of serotypes O63… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 42 publications
1
16
1
Order By: Relevance
“…The MLVA carried out in this work has a high discriminatory power which proved to be particularly useful in epidemiological studies (17). Serogroups O6, O153, O78, and O159 detected in our collection have been reported for ETEC isolates from other locations (3,4,36). However, strains reacting simultaneously with anti-O104 and anti-O127 sera are not commonly isolated and may represent a geographically confined group of strains.…”
Section: Discussionmentioning
confidence: 55%
“…The MLVA carried out in this work has a high discriminatory power which proved to be particularly useful in epidemiological studies (17). Serogroups O6, O153, O78, and O159 detected in our collection have been reported for ETEC isolates from other locations (3,4,36). However, strains reacting simultaneously with anti-O104 and anti-O127 sera are not commonly isolated and may represent a geographically confined group of strains.…”
Section: Discussionmentioning
confidence: 55%
“…In investigations conducted in Germany [181] and Brazil [100], STEC were isolated more frequently from diarrhoeic calves than from healthy calves. Conversely, other studies have reported higher rates of STEC faecal carriage in healthy than in diarrheic animals [9,141].…”
Section: Cattlementioning
confidence: 67%
“…Of these serogroups, O6, O8, O78, O114, O120, O148, O153 and O159 have frequently been associated with ETEC in previous studies [18][19][20] and these 8 O-groups were detected in 26 of the 43 ETEC strains. A small number of additional strains were of O serogroups that have infrequently been detected in ETEC strains, namely, O1, O41 and O21.…”
Section: Resultsmentioning
confidence: 99%